The level of administrative performance among the heads of academic departments in Palestinian university colleges and its relationship to the level of organizational commitment among their teaching staff members (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the level of administrative performance of the heads of academic departments in Palestinian university colleges and its relationship to the level of organizational commitment among members of its teaching staff, from the point of view of the faculty members, and using the descriptive / correlative approach, and referring to previous literature, a questionnaire was designed consisted of (60) items distributed on (10) axes: (administrative leadership, planning and organization, scientific and professional growth, evaluation and follow-up, human relations, decision-making, student affairs, emotional commitment, continuity commitment, and normative commitment), and after verifying its validity and stability, it was applied to a stratified random sample of (277) faculty members. The study concluded that the level of administrative performance of academic department heads was "medium", and the level of organizational commitment among faculty members was "significant". Also, there was a positive, statistically significant correlation at the significance level (α ≥ 0.05) between the level of administrative performance among heads of departments. The academic departments in Palestinian university colleges and the level of organizational commitment among their faculty members. The study recommended the need to enhance the reality of administrative performance among the heads of academic departments in Palestinian colleges through methods and means, including (training courses, workshops between former and new presidents, publications and scientific studies), and promoting the concept of the organizational commitment of faculty members at Palestinian university colleges, and raising its level by providing incentives and job benefits to them.
Keywords: administrative performance; organizational commitment; academic departments; university colleges; Palestine